(untitled) (Desarrollo Económico. Revista de Ciencias Sociales, 2023)
We claim that the overall effect of district magnitude on female representation is ambiguous because district magnitude increases both (a) party magnitude—which promotes the election of women, and (b) the number of lists getting seats—which hampers it, as marginal lists are usually headed by men. For identification, we exploit the fact that the Argentine Chamber of Deputies and the Buenos Aires legislature elect half of their members every two years, and thus some districts have varying magnitudes in concurrent and midterm elections. We find a positive but weak effect of district magnitude on female representation, which can be decomposed into a positive effect driven by party magnitude and a negative one channeled by the number of lists getting seats. We find similar results in a sample of seven Latin American countries.